Revolutionizing lymph node metastasis imaging: the role of drug delivery systems and future perspectives - Ze-Min Cai; Zi-Zhan Li; Nian-Nian Zhong; Lei-Ming Cao; Yao Xiao; Jia-Qi Li; Fang-Yi Huo; Bing Liu; Chun Xu; Yi Zhao; Lang Rao; Lin-Lin Bu (Journal of Nanobiotechnology, 2024)
Abstract The deployment of imaging examinations has evolved into a robust approach for the diagnosis of lymph node metastasis (LNM). The advancement of technology, coupled with the introduction of innovative imaging drugs, has led to the incorporation of an increasingly diverse array of imaging techniques into clinical practice. Nonetheless, conventional methods of administering imaging agents persist in presenting certain drawbacks and side effects. The employment of controlled drug delivery systems (DDSs) as a conduit for transporting imaging agents offers a promising solution to ameliorate these limitations intrinsic to metastatic lymph node (LN) imaging, thereby augmenting diagnostic precision. Within the scope of this review, we elucidate the historical context of LN imaging and encapsulate the frequently employed DDSs in conjunction with a variety of imaging techniques, specifically for metastatic LN imaging. Moreover, we engage in a discourse on the conceptualization and practical application of fusing diagnosis and treatment by employing DDSs. Finally, we venture into prospective applications of DDSs in the realm of LNM imaging and share our perspective on the potential trajectory of DDS development. Graphical Abstract